ANALISIS KOMODITI JAGUNG (ZEA MAYS L) - Asmina Herawaty Sinaga (Jurnal Darma Agung, 2018)
Competitiveness Analysis of Comodity Maize (Zea Mays L). Studi Case : Pancur Batu subdistrict , Deli Serdang , Sumatera Utara. Based on the test results of the research with the Policy Analysis Matrix (PAM) is obtained that: (a). Pripat Propitability ( PP ) = D =7.09998 million . means : sistem propit commodities gained at the expense of normal. (b) Sosial Propitability (SP) = H = 8722322 .means commodity corn has a comparative advantage (comparative advantage). (c) Komoditi corn in the study area has a competitive advantage. (d). Domestic Resource Cost Ratio (DRCR) = G/(EF) = 3,936,319 / 8,722,322 = 0.4513 < 1 means that the system implemented prosses a competitive advantage. (e). Output transper : OT = AE = 4290361 > 0 means no transper from the public to the manufacturer. (f). Protection .Nominal coeficient on Output (NPCO) = A/E = 0.7667 < 1 means that the goverment’s policy is not protective. (g). Transper Input (TI) = B – F = 1622343 > 0 means there transper input of agricultural producers to farmers in the form of tradable inputs. (h). Protection. Nominal Coeficient on Input (NPCI) = B/F = 0.6610 <1 means there is subsidy on tradable inputs. (i). Transper Factor (FT) = CG = 0 means no transper from farmers to manufacturers of non tradable inputs. (j). Effective Protection Coeficient (EPC) = (AB) / (EF) = 0814 < 1 then concluded protectivePolicy. (k). Net Transper (NT) = DH = 1622342 > 0 means no additional producer surplus due to government policy againist domestic agricultural commodities. (l). Profitability coefficient (PC) = D/H = 0.814 < 0 means that the government’s policy is not to provide incentives to producers. (m). Subsidy Ratio to Producer (SRP) = L/E = 1,622,342 / 18,391,130 = 0.0882 means that the proportion of revenues to the social price for a replacement policy is very low. (n). Usahatani corn in the area of research has been eisien.